Multiuser wireless smart parcel box - Jamaluddin, Muhammad Azamuddin; Abdul Aziz, Azlinda; Mohd Isa, Mohd Ali (College of Computing, Informatics, and Mathematics, 2025)
The Multiuser Wireless Smart Parcel Box is an innovative solution that addresses the issues of today's parcel distribution system, notably in terms of security, accessibility, and efficiency. This technology offers secure and automated parcel delivery by authenticating the receiver using a QR code, allowing only authorized people to access the parcel box. The integration of a Raspberry Pi, a Firebase database, and a mobile application allows for real-time monitoring and control, with users receiving notifications when parcels arrive. The device includes a servo motor to lock and unlock the box, a camera module for live streaming, and an LED light for visibility in low-light circumstances. HTTP requests provide network connectivity, allowing the mobile application and parcel box to cooperate seamlessly. The use of this smart parcel box lowers the danger of parcel theft, reduces delivery failures owing to recipients absence, and supports contactless and automated delivery procedure. Future developments will include improved security features through encryption, an upgrade to the locking mechanism, and the integration of additional sensors to improve functioning. This project represents a big step forward in upgrading last-mile delivery services by using IoT and smart technology to create a more secure and efficient parcel management system.